A bounds analysis of world food futures: Global agriculture through to 2050 - Pardey, Philip G.; Beddow, J.M.; Hurley, T.M.; Beatty, T.K.M.; Eidman, V.R. (Wiley, 2014)
The notion that global agricultural output needs to double by 2050 is oft repeated. Using a new International Agricultural Prospects (iAP) Model, to project global agricultural consumption and production, we find in favour of a future where aggregate agricultural consumption (in tonnes) increases more modestly, by around 69 per cent (1.3 per cent per year) from 2010 to 2050. The principal driver of this result is a deceleration in population growth in the decades ahead. Per capita income growth and changing demographics (generally ageing population) have significant but secondary roles in spurring growth in agricultural consumption, as does our projected growth in the use of agricultural feedstocks to meet the growth we envisage in biofuel demand. Worldwide (but not equally everywhere), crop yield growth has generally slowed over the past decade or so. Notwithstanding a projected continuance of this slowdown, the prospective improvements in crop productivity are still sufficient to reduce per capita cropland use, such that land devoted to crops would need to increase by less than 10 per cent. Even in our upper‐bound (high‐consumption) scenario, we estimate that there remains sufficient productive agricultural land to more than meet the demand without ploughing‐in additional forest‐dominated lands.